1988
DOI: 10.1002/1097-0142(19880615)61:12<2541::aid-cncr2820611225>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Solid cancer risk after treatment of Hodgkin's disease

Abstract: We pooled the data from seven studies of second cancer risk after treatment of Hodgkin's disease (HD) and estimated the relative risks (RR) of solid cancers (SC) for the following two treatment groups: (1) radiotherapy, with or without chemotherapy; and (2) chemotherapy alone. For all treatment groups combined, the RR of SC was 2.1 (95% confidence limits: 1.8 to 2.4). In the radiotherapy group, statistically significant RR were found for SC for all anatomic sites (RR: 2.2; 95% confidence limits: 1.9 to 2.6) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…It is known from several studies (Boivin and O'Brien, 1988;Tucker et al, 1988;Swerdlow et al, 1992;van Leeuwen et al, 1994), and unsurprising in the light of the findings in other radiation-exposed cohorts such as atomic bomb survivors (National Research Council, 1990), that solid cancer risks can be increased by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from several studies (Boivin and O'Brien, 1988;Tucker et al, 1988;Swerdlow et al, 1992;van Leeuwen et al, 1994), and unsurprising in the light of the findings in other radiation-exposed cohorts such as atomic bomb survivors (National Research Council, 1990), that solid cancer risks can be increased by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The risks after chemotherapy alone are much less clear, however. There have been relatively small numbers of person-years of long-term follow-up after chemotherapy without radiotherapy in most cohorts yet published, and until recently the power of such cohorts has been low and increased risk of solid cancers has not been seen (Boivin and O'Brien, 1988;Young et al, 1990). Four recent studies have shown increased solid cancer risk after chemotherapy (Kaldor et al, 1992;Swerdlow et al, 1992;Biti et al, 1994;Boivin et al, 1995) while others did not (Abrahamsen et al, 1993;van Leeuwen et al, 1994b).…”
Section: Discussionmentioning
confidence: 99%
“…After radiotherapy there are raised risks of several solid tumours (Boivin & O'Brien, 1988), and probably also of leukaemia (Boivin et al, 1984; Tucker et al, 1988;Van Leeuwen et al, 1989). After chemotherapy, a very high risk of acute or non-lymphocytic leukaemia has been shown (Pedersen-Bjergaard et al, 1987; Tucker et al, 1988), and in a recent study we found solid cancer risk also to be increased (Swerdlow et al, 1992).…”
mentioning
confidence: 90%
“…In addition, the estimated average follow-up period was only 3.6 years for the CT only patients, far shorter than for the RT and CT groups. 49 We therefore do not believe that the literature indicates a higher second malignancy risk exists after CMT than after single modality therapy.…”
Section: Risk Of Solid Tumorsmentioning
confidence: 99%